The Attitude and the Use of Mobile Phones Among Students - Kristiana Dewayani; Aristha Jaya Kusuma (International Conference of Mental Health, Neuroscience, and Cyber-psychology)
The use of mobile phones by students intended for various purposes such as camera, edit the document, download information, social media, and so on. Quantitative research aims to provide an overview of the attitudes and behavior of mobile use among students. The respondent 72 students from a private University in Depok, West Java. Research in methods of survey, the data collected by the scale of the Attitude and Behavior of Mobile Usage . The results of this research show that there is no difference in attitudes towards mobile between men and women, both in terms of ease of use, the benefits of using mobile phones as well as mobile usage frequency. Subsequent findings, the more positive attitude toward mobile phone, the more often students using mobile phone. Interesting things discovered that students who feel the use of mobile useful, does not correlate with the purchase of a data packet, while when the students find it easy to use mobile, followed by the high purchase of data packets. Similarly, in terms of the use of mobile phones as cameras, when the students find it easy to use mobile, then it will be more likely to use mobile phones as cameras.